2014
DOI: 10.1007/s40692-014-0011-0
|View full text |Cite
|
Sign up to set email alerts
|

A review of e-Learning policy in school education in Singapore, Hong Kong, Taiwan, and Beijing: implications to future policy planning

Abstract: The acceleration of e-Learning around the world has driven the major cities/regions in the Asia-Pacific region such as Singapore, Hong Kong, Taiwan, and Beijing to plan and implement official policies on e-Learning for enhancing the quality of school education. This article aims to review experiences and then draw lessons of these four major Asian cities/regions in the development of e-Learning policies on the dimensions of infrastructure, curriculum integration, students learning, teacher professional develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 16 publications
1
34
0
Order By: Relevance
“…Lastly, Taiwan placed distance education at the forefront of education policies. To this end, emphasis was placed on developing digital resources for K-12 education to be used by teachers, students and citizens, and to construct the hardware infrastructure necessary for distance education (Kong et al, 2014). Thus, it can be seen that even before the Covid-19 outbreak, distance education for K-12 was being implemented in countries around the world in such forms as digital campuses, online training, e-content, educational videos, mail, educational radio, DVDs, mobile phone connections and videoconferences in accordance with the needs and education policies of individual countries.…”
Section: Theoretical Background: Implementations Of Distance Education In K-12 Schools Around the Worldmentioning
confidence: 99%
“…Lastly, Taiwan placed distance education at the forefront of education policies. To this end, emphasis was placed on developing digital resources for K-12 education to be used by teachers, students and citizens, and to construct the hardware infrastructure necessary for distance education (Kong et al, 2014). Thus, it can be seen that even before the Covid-19 outbreak, distance education for K-12 was being implemented in countries around the world in such forms as digital campuses, online training, e-content, educational videos, mail, educational radio, DVDs, mobile phone connections and videoconferences in accordance with the needs and education policies of individual countries.…”
Section: Theoretical Background: Implementations Of Distance Education In K-12 Schools Around the Worldmentioning
confidence: 99%
“…The vigilant assessment of e-learning readiness postpones the implementation of e-learning. Yet one of the difficulties of adopting e-learning is the absence of appropriate consideration of the individual and organizational factors affecting e-learning readiness (Azimi, 2013; Kong, Chan, Huang, & Cheah, 2014). E-learning readiness, indeed, satisfies the needs of the implementers to trust technology through reassuring effective learning interactions.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Addressing e-learning readiness should allow both teachers and learners to accomplish their purposes in the most protected and confidential way. Assessment of security and policy elements provides more control over the learning process, with greater consideration toward learning pace and topics (Kong et al., 2014; Memene & Simmons, 2015). In their study of e-learning readiness and online learning environments, Lin et al.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…In the same context, Tairab, et al, demonstrated that ICT policy is one of the main factors that can drive the educational progress in K-12 education in Sudan (Tairab et al, 2016). In addition, in their study for e-learning policy- (Kong, Chan, Huang, & Cheah, 2014) identified five dimensions or factors to examine the status of the policy: (a) infrastructure, (b) curriculum integration, (c) student learning, (d) teacher professional development and leadership, and (e) capacity building. Before that, UNESCO identified an approach to IT policy and boosts that, this approach consists of "policy -curriculum, assessment resources, professional development, beside the fund generation" (Tilya, 2008).…”
Section: Influencing Factors For Ict Policymentioning
confidence: 96%
“…In 2001 china followed five years' strategy for ICT (2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015) (Kong et al, 2014). In addition to enhancing teachers' competencies, school infrastructure, learning resources, China is using OER, and looking forward.…”
Section: Ict Policy In Asiamentioning
confidence: 99%